PENGARUH AUDIT INTERNAL TERHADAP EFISIENSI PENGENDALIAN INTERNAL KREDIT PADA BRI KOTA KENDARI - Hardini, Hardini (JITAA : Journal Of International Taxation, Accounting And Auditing, 2023)
This study aims to determine the effect of internal audit on the efficiency of credit internal control at BRI Kendari City, data collection was carried out using a questionnaire. Data obtained from 24 people. Data analysis using simple regression. The results of the analysis show that Internal Audit has a significant effect on the efficiency of credit Internal Control at BRI Kendari City, because the previously proposed hypothesis is accepted. This can be seen from the sig t value of 0.000, when compared to the significant level of 0.05, the sig t value (0.000) < ? = 0.5 or this can be interpreted that the research hypothesis (H 0) proposed is proven to be acceptable that there is a significant influence between the Internal Audit variable on the Efficiency of Internal Control of credit at BRI Kendari City or in other words if it is rejected or H1 is accepted, so that a decision can be made to reject H0 and H1 is accepted.